2023
DOI: 10.1002/iid3.769
|View full text |Cite
|
Sign up to set email alerts
|

Complement component C1q initiates extrinsic coagulation via the receptor for the globular head of C1q in adventitial fibroblasts and vascular smooth muscle cells

Abstract: Background Vascular diseases are highly associated with inflammation and thrombosis. Elucidating links between these two processes may provide a clearer understanding of these diseases, allowing for the design of more effective treatments. The activation of complement component 1 (C1) is a crucial contributor to innate immunity and is associated with significant concentrations of circulating C1q. Many pathological pathways initiate when C1q interacts with gC1qR. This interaction plays a major role in inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“… 22 , 23 C1q contributes to coagulation by inhibiting platelet adhesion, IgG adsorption, and reducing the diffusion of adherent platelets. 24 Moreover, research indicates that C1q can directly influence blood coagulation. Bleeding experiments involving C1q-deficient mice and wild-type mice revealed that mice lacking C1q exhibited prolonged bleeding times and increased blood loss, underscoring the direct involvement of C1q in thrombosis during the coagulation process.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 C1q contributes to coagulation by inhibiting platelet adhesion, IgG adsorption, and reducing the diffusion of adherent platelets. 24 Moreover, research indicates that C1q can directly influence blood coagulation. Bleeding experiments involving C1q-deficient mice and wild-type mice revealed that mice lacking C1q exhibited prolonged bleeding times and increased blood loss, underscoring the direct involvement of C1q in thrombosis during the coagulation process.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of C1q with platelet surface receptors not only enhances platelet procoagulant activity through the expression of integrins and P-selectin but also promotes platelet adhesion to activated endothelial cells ( 74 76 ). The role of C1q in modulating the expression of TF in adventitial fibroblasts and coronary artery vascular smooth muscle cells via its binding to gC1qR further implicates it in thrombus formation and hemostasis regulation ( 77 ). Experimental findings, such as the prolonged bleeding and increased blood loss in C1q-deficient mice compared with wild-type animals, underline the direct involvement of C1q in coagulation processes, although the underlying mechanisms warrant further investigation ( 78 , 79 ).…”
Section: Discussionmentioning
confidence: 99%